Robert Schumann - Bauer, T. (artist):::Creator::::::::::::; Jäger, Carl, 1833-1887 (artist):::Contributor:::::::::::: (2020)
Portrait engraving of Robert Schumann by T. Bauer based on a portrait by Carl Jäger, ca. 1874.